Fresh fruit consumption and all-cause and cause-specific mortality: findings from the China Kadoorie Biobank - Du, H; Li, L; Bennett, D; Yang, L; Guo, Y; Key, T; Bian, Z; Chen, Y; Walters, R; Millwood, I; Chen, J; Wang, J; et al. (Oxford University Press, 2017)
Background Higher fruit consumption is associated with lower risk of cardiovascular disease (CVD). Substantial uncertainties remain, however, about its associations with all-cause mortality and mortality from subtypes of CVD and major non-vascular diseases, especially in Chinese population. Methods In 2004-08, the nationwide China Kadoorie Biobank Study recruited >0.5 million adults aged 30-79 years from 10 diverse localities in China. Fresh fruit consumption was estimated using an interviewer-administered electronic questionnaire and mortality data were collected from death registries. Among the 462,342 participants who were free of major chronic diseases at baseline, 17,894 deaths were recorded during ~ 7 years of follow-up. Cox regression yielded adjusted rate ratios (RRs) for all-cause and cause-specific mortality associated with fruit consumption. Results At baseline, 28% of participants reported consuming fruit ≥4 days/week (regular consumers) and 6% reported never/rarely consuming fruit (non-consumers). Compared with non-consumers, regular consumers had 27% (RR=0.73, 95% CI 0.70-0.76) lower all-cause mortality, 34% lower CVD mortality (n=6166; RR=0.66, 0.61-0.71), 17% lower cancer mortality (n=6796; RR=0.83, 0.78-0.89), and 42% lower mortality from chronic obstructive pulmonary disease (COPD, n=1119; RR=0.58, 0.47-0.71). For each, there was an approximately log-linear dose-response relationship with amount consumed. For mortality from site-specific cancers, fruit consumption was inversely associated with digestive tract cancer (n=2265; RR=0.72, 0.64-0.81), particularly oesophageal cancer (n=801; RR=0.65, 0.50-0.83), but not with cancers of lung and liver. Conclusions Among Chinese adults, higher fresh fruit consumption was associated with significantly lower mortality from several major vascular and non-vascular diseases. Given the current low population level of fruit consumption, substantial health benefits could be gained from increased fruit consumption in China.